1990
DOI: 10.1002/cne.902950408
|View full text |Cite
|
Sign up to set email alerts
|

Organization of cortical, basal forebrain, and hypothalamic afferents to the parabrachial nucleus in the rat

Abstract: In a previous study (Herbert et al., J. Comp. Neurol. [1990];293:540-580), we demonstrated that the ascending afferent projections from the medulla to the parabrachial nucleus (PB) mark out functionally specific terminal domains within the PB. In this study, we examine the organization of the forebrain afferents to the PB. The PB was found to receive afferents from the infralimbic, the lateral prefrontal, and the insular cortical areas; the dorsomedial, the ventromedial, the median preoptic, and the paraventri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

39
235
0
1

Year Published

1996
1996
2012
2012

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 373 publications
(275 citation statements)
references
References 82 publications
39
235
0
1
Order By: Relevance
“…Our findings in the present study are entirely consistent with their results. In the rat and golden hamster, the external subdivision of the LPb was reported to project extensively to the basal forebrain region including to the Amy and the hypothalamus (Fulwiler and Saper, 1984;Moga et aL, 1990;Halsell, 1992). Based on a physiological study, electrical or chemical stimulation of this region should produce profound pressor, tachycardic, and tachypneic responses in the rat .…”
Section: Projections From the Apmentioning
confidence: 99%
“…Our findings in the present study are entirely consistent with their results. In the rat and golden hamster, the external subdivision of the LPb was reported to project extensively to the basal forebrain region including to the Amy and the hypothalamus (Fulwiler and Saper, 1984;Moga et aL, 1990;Halsell, 1992). Based on a physiological study, electrical or chemical stimulation of this region should produce profound pressor, tachycardic, and tachypneic responses in the rat .…”
Section: Projections From the Apmentioning
confidence: 99%
“…From the NST, ascending gustatory fibers project to third-order taste cells within the PbN of the pons (7,22,42,46,(53)(54)(55)87). Two separate routes carry taste information from the PbN further to the forebrain taste areas and cortex: the ventral forebrain pathway that involves the central nucleus of the amygdala (CeA), the lateral hypothalamus (LH), the bed nucleus of the stria terminalis (BNST), the substantia innominata (3,12,16,21,31,33,34,41,47,63,64,71); and the thalamocortical pathway that is characterized by the involvement of the bilateral VPMpc, which, in turn, carries taste information to the gustatory cortex (GC) (5,25,45,48,51).The PbN is a critical neural substrate for a number of taste-guided behavioral or physiological responses, including conditioned taste aversion learning (CTA), gastric distension, and sodium appetite. It has been demonstrated that a subpopulation of neurons in the PbN can be coactivated by both gustatory and vagal (hepatic) stimulation (26) or gustatory and gastric distension (1), indicating that the PbN is the locus of integration for gustatory and other vagal afferent inputs.…”
mentioning
confidence: 99%
“…Second, studies of immediate early gene activation have shown that various limbic structures, including the lateral septum, are activated by intracerebroventricular CRH (Arnold et al, 1992;Imaki et al, 1993). Third, the septum shows strong connections to areas implicated in stress responses, such as the paraventricular nucleus of the hypothalamus, the dorsal raphe nucleus, and the locus coeruleus (Swanson and Cowan, 1979;Silverman et al, 1981;Sawchenko and Swanson, 1983;Moga et al, 1991;Staiger and Nürnberger, 1991). The medial septum has a direct projection to the amygdala, whereas the lateral septum has both a direct projection and a more extensive indirect projection to the amygdala (Meibach and Siegel, 1977;Russchen, 1982;Dudley et al, 1990;Volz et al, 1990;Staiger and Nürnberger, 1991).…”
mentioning
confidence: 99%